A comprehensive review of the pathogenic mechanisms of Pseudomonas aeruginosa: synergistic effects of virulence factors, quorum sensing, and biofilm formation - Zhang, Xindan; Zhang, Duo; Zhou, Di; Zheng, Shuai; Li, Shuang; Hou, Qinlong; Li, Gen; Han, Huiming (Frontiers in Microbiology, 2025)
Pseudomonas aeruginosa (P. aeruginosa) is a ubiquitous opportunistic pathogen and a major cause of nosocomial infections worldwide. It can provoke a spectrum of clinical manifestations-ranging from postoperative wound infections, pressure ulcers, abscesses, and otitis media to life-threatening bacteremia and sepsis, especially in burn patients. Over the past decade, extensive research has elucidated its complex virulence repertoire, including exotoxins, proteases, and siderophores; the hierarchical Quorum Sensing (QS) networks; and its robust capacity for biofilm formation. In this review, we consolidate significant studies published since 2015 to develop a comprehensive framework elucidating the virulence mechanisms of P. aeruginosa. Beyond cataloging individual factors, we highlight how QS regulators coordinate toxin production and biofilm maturation, and how these processes converge to facilitate immune evasion. We further examine cross-talk between QS circuits (Las, Rhl, and Pqs), their response to environmental cues, and the modulatory role of host signals. Despite these advances, significant gaps remain: the spatiotemporal interplay among different virulence modules; the precise molecular triggers of biofilm dispersal; and the dynamics of bacterial–host immune interactions in vivo. Notably, targeting QS with small-molecule inhibitors has shown promise in attenuating pathogenicity, yet translating these findings into clinical therapies requires more nuanced understanding of resistance emergence and host microbiome effects. We propose that future investigations prioritize (1) the structural biology of QS receptors to guide rational inhibitor design; (2) single-cell and organ-on-a-chip models to dissect biofilm heterogeneity; (3) dual-omics approaches to map host–pathogen signaling crosstalk; and (4) environmental modulators-such as iron availability and shear stress-that fine-tune virulence expression. Such multidisciplinary efforts will underpin the development of next-generation anti-virulence therapies, ultimately improving prevention and treatment of P. aeruginosa infections and safeguarding public health.